Preliminary Study of the Applicability of Software in the Investigation of Sustained Auditory Attention - Feniman, Mariza Ribeiro; José, Maria Renata; Mondelli, Maria Fernanda Capoani Garcia; Abramides, Dagma Venturini Marques; Lauris, José Roberto Pereira; Salvador, Karina Krähembühl; Cavalheiro, Maria Gabriela; Maximino, Luciana Paula (International Archives of Otorhinolaryngology, 2022)
Introduction The use of auditory behavioral tests, which specifically assess sustained attention, is necessary, due to its relationship with learning, language production, cognitive development and school performance.Objective To evaluate how children performed using software developed to investigate the ability of sustained auditory attention, and to compare the scores obtained in this format with those of the original, non-computerized test.Methods This cross-sectional study included 52 children of both genders, aged 6 to 11 years, with normal hearing and no history of complaints regarding inattention and/or hyperactivity. The computerized test was administered to all 52 children. The total error score (inattention and impulsivity) and the vigilance decrement were used to define the children's performance when using the software. The scores obtained in the two formats (computer software and original on compact disc) were then compared.Results Statistically significant differences were found in the scores for innattention, impulsivity, and total error score (inattention and impulsivity) when comparing genders, and a negative correlation coefficient was found when comparing ages. Increased scores were found for all variables of the sustained auditory attention ability test (SAAAT) compared with the original format.Conclusion Females performed worse than males in all aspects except for vigilance decrement when using the SAAAT software developed to evaluate the ability of SAAAT vigilance; younger children made more errors when using the SAAAT software; inattention errors were more frequent than impulsivity. Overall, higher values were obtained using the SAAAT software, when compared with the original version.
Keywords: attention; children; aptitude; evaluation study; software